2006
DOI: 10.1002/marc.200600221
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 5‐Fluorouracil‐Poly(L‐lactide) Microparticles Using Solution‐Enhanced Dispersion by Supercritical CO2

Abstract: Summary: 5‐Fluorouracil‐poly(L‐lactide) (5‐Fu‐PLLA) microparticles have been prepared by an SEDS process. First, the 5‐Fu is successfully micronized and is then used to produce the 5‐Fu‐PLLA microparticles. The 5‐Fu‐PLLA microparticles synthesized by the SEDS process exhibit a rather spherical shape and a narrow particle size distribution, where it ranges from 615 to 1 990 nm, with a mean particle size of 980 nm. The dichloromethane residue in the 5‐Fu‐PLLA microparticles without any further treatment is 46 pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 22 publications
1
38
1
Order By: Relevance
“…The research groups of Ghaderi, Lee, and Rantakyla, had reported their findings on the preparation of PLA and copolymer microparticles via SAS process separately [13,22,25]. In our previous studies [36,37], we had succeeded in micronizing PLLA with various molecular weight using different processing conditions, and loading 5-Fluorouracil into PLLA microparticles, via SEDS process. However, to our knowledge, few researchers reported that paclitaxel was encapsulated into PLA-PEG-PLA triblock copolymer microparticles by scCO 2 technique in the SEDS process.…”
Section: Introductionmentioning
confidence: 96%
“…The research groups of Ghaderi, Lee, and Rantakyla, had reported their findings on the preparation of PLA and copolymer microparticles via SAS process separately [13,22,25]. In our previous studies [36,37], we had succeeded in micronizing PLLA with various molecular weight using different processing conditions, and loading 5-Fluorouracil into PLLA microparticles, via SEDS process. However, to our knowledge, few researchers reported that paclitaxel was encapsulated into PLA-PEG-PLA triblock copolymer microparticles by scCO 2 technique in the SEDS process.…”
Section: Introductionmentioning
confidence: 96%
“…25,26 Curcumin is widely used as an anticancer agent in preclinical and clinical trials, probably due to their capability of generating intracellular ROS. However, this drug is poorly soluble in water, which restricts it from being directly used in aqueous solutions.…”
Section: Discussionmentioning
confidence: 99%
“…24 5-Fluorouracil (5-FU) is another highly efficient chemotherapeutic agent that inhibits the methylation reaction of deoxyuridylic acid to thymidylic acid. 25,26 This chemical drug can cause intense thymine deficit in the cells by interfering with the synthesis of deoxyribonucleic acid and ribonucleic acid, which eventually results in an imbalanced growth and death of cancer cells. To increase their water solubility and biocompatibility, several drug carriers are developed based on nanotechnology, 27 ranging from liposome, 28 proteins, 29 saccharides, 30 phospholipids, 31 to inorganic silica particles 32,33 and polymeric organic nanoparticles.…”
mentioning
confidence: 99%
“…Solution-enhanced dispersion by supercritical fluids (SEDS) is one of the SFP processes that have attracted high attention in producing high-quality drug composite microparticles. Some successful examples include: composite crystals of acetaminophen and p-acetoxyacetanilide [6], budesonide-b-cyclodextrin complexes [7], microencapsulation of amoxicillin in poly(L-lactic acid) [8], 5-fluorouracil-poly-(L-lactide) microparticles [9], budesonide-c-cyclodextrin complexes [10], etc. In our previous works, the SEDS-prefilming atomization (PA) process has been also successfully applied to deposit the composite microparticles of polyethylene glycol (PEG) loaded with natural carotene [2] and caroteneproanthocyanidin composite microparticles [11].…”
Section: Introductionmentioning
confidence: 99%